The role of observation, cognition, and imagination in Keynes's approach to decision-making - Felipe Almeida; Marcelo Curado (EconomiA, 2019)
The search for psychological content or support for economic decision-making is a subject that is contemporaneously stressed. Considering Keynesian and Post-Keynesian economics, it is possible to perceive several approaches that reclaim behavioral economics as a psychological support for decision-making. This study follows a different procedure. It points out the psychological issues studied by Keynes and introduces psychological theories that analyze these issues in order to emphasize psychological support for Keynes's approach to decision-making. In doing so, this study relies on the role of observation, cognition, and imagination in the Keynesian perspective on decision-making.
Keywords: B50; B59; 330; Cognition; Imagination; Keynesian decision-making; Observation; Vicarious learning